2012
DOI: 10.2478/v10007-012-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Simple RP-HPLC method for determination of triple drug combination of valsartan, amlodipine and hydrochlorothiazide in human plasma

Abstract: Hypertension is emerging as one of the most significant health complications in recent years (1). There has been a marked increase in the use of combinations of antihypertensive drugs as well with complementary mechanisms of action, with the aim of reducing blood pressure levels more rapidly and improving treatment compliance. The A simple RP-HPLC method for the quantification of valsartan (VAL), amlodipine (AML) and hydrochlorothiazide (HCT) in human plasma was developed and validated. VAL, AML and HCT were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…To the best of our knowledge, there are only four methods which describe their simultaneous analysis in pharmaceutical preparations [42] , [43] and human plasma [42] , [43] , [44] , [45] . The salient features of these methods are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only four methods which describe their simultaneous analysis in pharmaceutical preparations [42] , [43] and human plasma [42] , [43] , [44] , [45] . The salient features of these methods are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…HPLC with UV detectors are easy to handle. The HPLC methods with photodiode array (PDA) and UV detectors have also been reported for the extraction of valsartan from the human plasma [1,18,19] .…”
Section: Several Bioanalytical Methods Have Been Reportedmentioning
confidence: 99%
“…The flow rate and stationary phase used were 1.0 ml/min and Gemini C 18 (250×4.6 mm i.d., particle size 5 µm) column (Phenomenex ® , USA) protected with C 18 (4×2 mm i.d.) guard column, respectively [19] . However, these existing HPLC-UV and HPLC-PDA methods involved multiple steps of extraction and use of expensive gases (such as nitrogen) for evaporation of organic solvents.…”
Section: Several Bioanalytical Methods Have Been Reportedmentioning
confidence: 99%
“…Literature survey revealed that few analytical methods based on HPLC [7][8][9][10][11][12] are reported for the determination of valsartan in biological samples. Conventional HPLC methods have the limitations in chromatographic run time, specificity and sensitivity compared with LC-MS/MS methods.…”
Section: Introductionmentioning
confidence: 99%